Pollen viability of Tepary bean (Phaseolus acutifolius A. Gray.) mutant lines under water stress conditions and inoculation with rhizobia - Crespo Muñoz, Sergio; Rivera Peña, Mariela; Rosero Alpala, Deisy Alexandra; Muñoz Flórez, Jaime Eduardo; Rao, Idupulapati M.; Muñoz Flórez, Ligia Carmenza (Universidad Nacional de Colombia, 2018)
Tepary bean, Phaseolus acutifolius A. Gray, is tolerant to drought and high temperatures but has low genetic diversity in its cultivated forms. To increase this diversity, a research program on mutation induction was initiated. The aim of this study was to establish the effect of different agro-morpho-physiological parameters on pollen viability and quantity in 123 mutant lines M5 of P. acutifolius and parental genotypes, by processing micrographs of pollen stained with acetocarmine. The experiment was conducted under greenhouse conditions and the experimental design was a split-split plot with three replicates; in addition, the factors evaluated were as follows: soil moisture conditions, inoculation with Bradyrhizobium sp. or Rhizobium tropici, and the evaluated lines (6 mutants and 2 non-mutants). The experiment was carried out maintaining night temperature above 25°C. There were no significant differences among treatments, and there was a positive correlation of pollen viability with other variables.